2018
DOI: 10.1088/1742-6596/1049/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Capital Management Practices on Employees’ Job Performance

Abstract: Abstract.This paper aims to analyze the relationship between the human capital management (HCM) practices which include training and development, recruitment and selection, Performance appraisal and employee's job performance in the telecom sector of Pakistan. To find the influence of HCM practices on employees job performance within telecom sector of Pakistan. This is a survey based research study. The sample of the study is employees' who are working in public and private sector telecommunication companies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…The findings revealed that extensive training has a stronger influence on job performance than selective staffing. The findings were consistent with the study of Zeb et al (2018a), which asserts that much of work performance is an attribute of enough extensive training programs. Training programs should be conducted at PTCL to improve employee knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…The findings revealed that extensive training has a stronger influence on job performance than selective staffing. The findings were consistent with the study of Zeb et al (2018a), which asserts that much of work performance is an attribute of enough extensive training programs. Training programs should be conducted at PTCL to improve employee knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…The organizations focusing on the development of human capital result in higher performance of their employees (Chadwick, 2017). The organizations adopt appropriate HPWS to develop human capital that results in higher level of performance (Subramony et al , 2018; Zeb et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The analyses performed pointed out a positive correlation between academic human capital and their salaries. Zeb, Abdullah and Javaid (2018) analysed the relationship between human capital management (which includes selection, recruitment, training and development), employee job performance, and performance appraisal in the telecom sector of Pakistan. To discover the influence of human capital management practices on the job performance of employees, a study of Asiaei and Jusoh (2015) analysed the contribution of intellectual capital in enhancing firm performance in Tehran.…”
Section: Literature Reviewmentioning
confidence: 99%